2000
DOI: 10.1088/0953-8984/12/8a/336
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic scaling in surface-controlled colloidal aggregation

Abstract: In this work, the aggregation behaviour of surface-modified colloidal particles was studied. In view of this, a method was developed which allows the dynamic scaling functions s (t ) and (x ) to be calculated from single-cluster light scattering data. The method was employed to investigate the aggregation of colloidal particles covered with different amounts of bovine serum albumin (BSA). It was found that BSA molecules do not alter the aggregation regime when the samples aggregate at the protein's isoelectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…A close inspection of the data in Figure 2 reveals, at certain temperatures and surfactant concentrations, a deviation from the power law behavior at early times. This type of divergence at early aggregation stages has previously been reported 35,36 from studies of colloidal aggregation in other systems, and this failure is…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…A close inspection of the data in Figure 2 reveals, at certain temperatures and surfactant concentrations, a deviation from the power law behavior at early times. This type of divergence at early aggregation stages has previously been reported 35,36 from studies of colloidal aggregation in other systems, and this failure is…”
Section: Resultssupporting
confidence: 73%
“…It has been speculated 46 that the reason for this numerical difference may be that the latter experiments of slow aggregation were conducted in a regime between DLCA and RLCA. Furthermore, in some studies , a continuous change of λ from ≈0 to ≈1 was observed in going from fast to slow aggregation.…”
Section: Resultsmentioning
confidence: 98%
“…Cluster assembly routes offer the advantage of uniform size distributions and sub-ten nanometer size ranges. Colloidal methods have been widely used to make nanoscale particles of many different materials [8,9], and recently to produce exchange-spring permanent magnets in the Fe 3 Pt/FePt system [10]. Here, energy products of isotropic magnets reached approximately 20 MGOe.…”
Section: Introductionmentioning
confidence: 99%